The relationship between socially responsible human resource management and moral voice in the Vietnamese public sector: does moral identification matter? - Minh-Tri Ha; Bao-Son Doan (Cogent Social Sciences, 2025)
This study offers an innovative examination of the correlation between socially responsible human resource management (SRHRM) and moral voice (MV) within Vietnam’s public sector, a context inadequately addressed in current literature. It specifically investigates the mediating functions of moral identity (MI) and moral identification (MOI), as well as the moderating function of behavioural integrity (BI). This research is important as it elucidates the gap in comprehension regarding how SRHRM affects MV through particular mediating and moderating mechanisms. Employing social identity theory (SIT) and structural equation modelling (SEM) on data from 434 employees, gathered through cluster sampling in Tien Giang Province, Vietnam, the study demonstrates that SRHRM significantly influences MV, with MOI acting as a partial mediator. This research innovatively examines the sequential mediating effects of MI and MOI, along with the moderating influence of BI in the SRHRM-MV relationship. The study contributes by thoroughly analysing the interaction of MI, MOI, and BI in the nexus between SRHRM and MV in Vietnam’s public domain. This offers theoretical progress in human resource management research and practical guidance for improving ethical conduct in public organisations.